HIV infection in patients with sexually transmitted infections in Zimbabwe - Results from the Zimbabwe STI etiology study. - Peter H Kilmarx; Elizabeth Gonese; David A Lewis; Z Mike Chirenje; Beth A Tippett Barr; Ahmed S Latif; Lovemore Gwanzura; H Hunter Handsfield; Anna Machiha; Owen Mugurungi; Cornelius A Rietmeijer (PLoS ONE, 2018)
Background HIV and other sexually transmitted infections (STI) frequently co-occur. We conducted HIV diagnostic testing in an assessment of the etiologies of major STI syndromes in Zimbabwe. Methods A total of 600 patients were enrolled at six geographically diverse, high-volume STI clinics in Zimbabwe in 2014-15: 200 men with urethral discharge, 200 women with vaginal discharge, and 100 men and 100 women each with genital ulcer disease (GUD). Patients completed a questionnaire, underwent a genital examination, and had specimens taken for etiologic testing. Patients were offered, but not required to accept, HIV testing using a standard HIV algorithm in which two rapid tests defined a positive result. Results A total of 489 participants (81.5%) accepted HIV testing; 201 (41.1%) tested HIV-1-positive, including 16 (11.9%) of 134 participants who reported an HIV-negative status at study enrollment, and 58 (28.2%) of 206 participants who reported their HIV status as unknown. Of 147 who self-reported being HIV-positive at study enrollment, 21 (14.3%) tested HIV negative. HIV infection prevalence was higher in women (47.3%) than in men (34.8%, p<0.01), and was 28.5% in men with urethral discharge, 40.5% in women with vaginal discharge, 45.2% in men with GUD, and 59.8% in women with GUD (p<0.001). Conclusions The high prevalence of HIV infection in STI clinic patients in Zimbabwe underscores the importance of providing HIV testing and referral for indicated prevention and treatment services for this population. The discrepancy between positive self-reported and negative study HIV test results highlights the need for operator training, strict attention to laboratory quality assurance, and clear communication with patients about their HIV infection status.